Lower limb joint replacement in rheumatoid arthritis - Clement, Nicholas D.; Breusch, Stephen J.; Biant, Leela C. (Journal of orthopaedic surgery and research, 2012)
There is limited literature regarding the peri-operative and surgical management of patients with rheumatoid disease undergoing lower limb arthroplasty. This review article summarises factors involved in the peri-operative management of major lower limb arthroplasty surgery for patients with rheumatoid arthritis.
Gesehen am 10.08.2018